Social Network Rumor Propagation Model Considering Blockchain Content Consensus - Zhang, Can (International Journal of Computer Science and Information Technology, 2025)
In order to better explore the information dissemination characteristics of social networks, a trust evaluation mechanism is constructed based on the consensus mechanism and incentive mechanism of blockchain, and the participation consensus probability function is introduced, and a rumor propagation model of blockchain social networks is proposed. In the experimental simulation, the influence of trust degree on consensus participation probability and rumor acceptance probability is quantified, and the influence of this model on rumor propagation is explained through the analysis of consensus probability and propagation probability, and the comparison with the existing model is made. The experimental results show that the propagation range of the proposed model is reduced by 12%-41% compared with the classical model, which verifies that the proposed model can effectively suppress rumor propagation.